Conselho Municipal de Assistência Social: um cenário de representação - Magnagnagno, Janete Krack (2012)
The aim of this work is to analyze the political representation presents in the Social Welfare municipal council, located in the Foz do Iguaçu city, Paraná state in Brazil. The Councils managers express the expansion of different forms of civil society participation in public administration and have introduced new forms of political representation, performed by civil society and government actors that proposes themselves to act in this instance as representatives of a specific segment. In accordance with the specific literature, the studies of political representation considers some types of representation: The mandate, the virtual , the advocacy, the discursive, the affinity and the contingent. The discussion about political representation has been realized around the dichotomies that involves some questions: Is the legitimacy of the representative action based in the authorization or there are other forms of legitimacy? Does the representativeacts on the interests of the group that it represents or its action is free? Are there mechanisms that can control and sanction the representatives? Is the mandate revoked? In this context, this study considers that the setting of the political representation presents in this Council recognizes that the political representantion is legitimed by three essential criteria: the affinity, authorization and the relation with social organization. This process results in a representation that presents the limits that are involved in the sharing power between government and civil society.